Asymptotic solution of a harmonic contact problem for a permeable stamp on a liquid saturated base - Gomilko, A.M.; Savitsky, O.A.; Trofimchuk, A.N. (Нелінійні коливання, 2002)
A plane harmonic problem of vertical vibrations of a rigid permeable stamp on a liquid saturated poroelastic base is considered. The equations of two-phase Biot media, taking into account inertial and viscous interactions of phases, are used. The asymptotic properties of the contact stress in dependence on small frequency of vibration are studied. Розглянуто гармонiчну задачу про вертикальнi коливання жорсткого проникного штампа на пористо-пружнiй основi, насиченiй рiдиною. Використано рiвняння для двофазних середовищ Bio з урахуванням iнерцiйних та в’язких взаємодiй мiж фазами. Дослiджено низькочастотнi асимптотичнi властивостi контактної напруги.